Interpersonal dependence and differential types of reflection in students – boys and girls - O. V. Myloslavska (Law and Safety)
The article presents results of the study of interpersonal dependence in the context of reflection as a necessary condition for personal autonomy and the mechanism of constructing and organizing a life perspective in adolescence.